Penguatan Kapasitas Ibu Rumah Tangga Melalui Pemanfaatan Tanaman Obat Keluarga di Desa Kerinjing Kecamatan Tanjung Raja Kabupaten Ogan Ilir - Ahmad Maulana; Nurkardina Novalia; Wahyu Aji Wijaya (Penerbit Goodwood, 2021)
Purpose: The Community Service Program (PKM) is located in Kerinjing Village, Tanjung Raja District, Ogan Ilir Regency. The targeted target audiences are housewives in the village. This activity aims to: (1) socialize the potential benefits of family medicinal plants (TOGA) as healthy drinks that can increase income, (2) socialize the correct way of planting family medicinal plants so that the quality is better, arousing the motivation of the target community to develop family medicinal plat processing. Method: The methods applied in this training include counseling on several theories that support the potential and composition of family medicinal plants, how to plant and process medicinal plants into various beverage processed products, suitable packaging methods, practice, and assistance. Community service activities are carried out through lectures and demonstrations. Results: The output produced from this activity include: (1) increased knowledge and skills of housewives regarding the use and processing of family medicinal plants, (2) increased knowledge of how to plant and pack good products, and (3) increased motivation for developing a business to use family medicinal plants. Conclusions: After the activity, there is an increase in knowledge and skills to develop a business to use family medicinal plants, their potential, and how to process them into healthy drink products, as well as proper packaging methods. In addition, this activity also increases the motivation of housewives who are participants to develop businesses in the field of beverage products based on family medicinal plants.